RESPON TANAMAN BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN JENIS MULSA DAN JENIS PUPUK ORGANIK LIMBAH TERNAK - Rahma, Meci Yuniastuti; Syafrullah, Syafrullah; Hawayanti, Erni; Mitori, Syaifullah (Universitas Muhammadiyah Palembang, 2021)
This study aims to determine the type of mulch and the type of organic fertilizer from livestock waste that have the best effect on the growth and production of shallot (Allium ascalonicum L). This study used an experimental method with a split plot design consisting of 9 combinations which were repeated 3 times so that 27 plots and 5 sample plants were obtained. The treatment in question is as follows: Factor I = Mulch Type (M) consisting of 3 replications: M0 = No Mulch, M1 = Jengkol Bark Mulch, M2 = Rice Husk Organic Mulch. Factor II = Types of Livestock Waste (K) consisting of 3 replications: K0 = without livestock waste fertilizer, K1 = Chicken Manure Organic Fertilizer, K2 = Chicken Manure Organic Fertilizer. The variables observed in this study were plant height (cm), number of leaves (strands), number of tubers per clump (tuber), tuber weight per clump (grams), tuber weight per plot (grams). The combination treatment between rice husk organic mulch and organic fertilizer from chicken manure gave the highest effect on the growth and production of shallots at 1.09 kg/plot or equivalent to 10.90 tons/ha.